(untitled) (KIUT Publication, 2025)
The article analyzes the theoretical and practical aspects of using automated systems in water resource management. Strategies for the efficient use of water resources based on the principles of the circular economy have been developed. Using international experience as an example, the advantages of automated management systems and the possibilities of their implementation in the context of Uzbekistan are examined. The article substantiates the economic and environmental efficiency of automated systems in the effective management of water resources.